Inhibitory Effect of Foscarnet and Acyclovir on Reproduction of Human Herpesvirus 6 in Cell Culture - A. V. Melnichenko; N. D. Lvov; G. A. Galegov (Антибиотики и Химиотерапия)
Two practically important antiviral agents, i. e. foscarnet (phosphonoformic acid, foscavir) and acyclovir, and their inhibitory effect on reproduction of human herpesvirus 6 (HHV-6) were investigated in an experiment with sensitive lymphoblastoic cell line HSB-2. Phosphonoformic acid (PFA) was shown advantageous vs. acyclovir. In a model of HHV-6 infection acyclovir was low active (chemotherapeutic index of 0.9) and its use in clinical practice is not useful, whereas PFA (chemoterapeutic index of 10) and similar agents showed significant antiviral activity that indicated the necessity of their further investigation.